2007
DOI: 10.1016/j.joca.2006.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan–glycerol phosphate/blood implants increase cell recruitment, transient vascularization and subchondral bone remodeling in drilled cartilage defects

Abstract: These results suggest that the greater levels of provisional tissue vascularization and BR activity are main factors supporting improved cartilage repair when chitosan-GP/blood implants are applied to marrow-stimulated cartilage lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
170
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(180 citation statements)
references
References 39 publications
(62 reference statements)
9
170
0
1
Order By: Relevance
“…In this study, the peak expression of mRNA including BSP, OCN, Runx2, and Col1 were observed at 2 weeks after extraction. These results seemed to be also consistent with previous studies 34,35) . Liu et al 35) reported that osteoblastic differentiation marker such as TGF-β1, BMP-2 and VEGF had peak expression level after 2 weeks.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, the peak expression of mRNA including BSP, OCN, Runx2, and Col1 were observed at 2 weeks after extraction. These results seemed to be also consistent with previous studies 34,35) . Liu et al 35) reported that osteoblastic differentiation marker such as TGF-β1, BMP-2 and VEGF had peak expression level after 2 weeks.…”
Section: Discussionsupporting
confidence: 94%
“…They concluded that cells on chitosan coating had higher proliferation, type 1 collagen deposition, and degree of mineralization compared to the control. Chevrier et al 34) reported that chitosan increased vascularization and induced granulation tissue generation. At 2 weeks after operation, a mixture of woven bone and fibrous tissue was seen in treated defects, whereas in untreated ones, the fibrous tissue was dominant.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated various effects of chitosan on bone healing and raised some hypotheses on its mechanisms [35,36,37]. For instance [38], observerd that chitosan increases the vascularization of blood vessels and stimulates budding tissue (tissue comprising of budding capillaries and fibroblasts) [6,38] noted that the mechanical strength of scaffold decreases with porosity. This might have led to longer healing time of the chitosan/gum arabic nanoparticle in comparison with chitosan.…”
Section: In-vivo Analysismentioning
confidence: 99%
“…Although rabbit model has been occasionally criticized as a cartilage repair model, these criticisms are often due to the use of skeletally immature animals which heal much more easily than mature animals that are quite useful in cartilage repair studies. 23,24 We have also recently compared subchondral bone structure in rabbit to human where a surprisingly similar thickness of the bone plate at $200-300 mm and porosity at $60% were observed in both species. Although the dimensions and choice of species in our study are well justified, our customized MF awl has a ledge to control hole depth (Fig.…”
Section: Microfracture Vs Drilling For Cartilage Repairmentioning
confidence: 99%
“…20 Bone remodeling can proceed along with the induction of chondrogenisis that resembles endochondral ossification, to form new bone in deeper zones and fibrous or fibrocartilaginous tissues in the more superficial chondral region. 10,14,15,21 A number of studies using bone marrow stimulation have been carried out to improve cartilage repair by modifying the perforation technique, 12 combining with periosteal grafts, 22 hybrid implants, [23][24][25] scaffolds, 26 or other surgical methods. 27 However, to our knowledge, no previous study has specifically investigated the characteristics of the acute fractures themselves, such as hole shape, extent of hematoma, extent of bone damage, morphology of fractured bone and bone marrow, and osteocyte necrosis.…”
mentioning
confidence: 99%